Studies on the contribution of PPAR Gamma to tuberculosis physiopathology - Díaz, Ariana; D’Attilio, Luciano; Penas, Federico; Bongiovanni, Bettina; Massa, Estefanía; Cevey, Agata; Santucci, Natalia; Bottasso, Oscar; Goren, Nora; Bay, María Luisa (Frontiers in Cellular and Infection Microbiology, 2023)
Introduction Tuberculosis (TB) is a major health problem characterized by an immuno-endocrine imbalance: elevated plasma levels of cortisol and pro- and anti-inflammatory mediators, as well as reduced levels of dehydroepiandrosterone. The etiological agent, Mycobacterium tuberculosis (Mtb), is captured by pulmonary macrophages (Mf), whose activation is necessary to cope with the control of Mtb, however, excessive activation of the inflammatory response also leads to tissue damage. Glucocorticoids (GC) are critical elements to counteract the immunoinflammatory reaction, and peroxisome proliferator-activated receptors (PPARs) are also involved in this regard. The primary forms of these receptors are PPARϒ, PPARα, and PPARβ/δ, the former being the most involved in anti-inflammatory responses. In this work, we seek to gain some insight into the contribution of PPARϒ in immuno-endocrine-metabolic interactions by focusing on clinical studies in pulmonary TB patients and in vitro experiments on a Mf cell line. Methods and results We found that TB patients, at the time of diagnosis, showed increased expression of the PPARϒ transcript in their peripheral blood mononuclear cells, positively associated with circulating cortisol and related to disease severity. Given this background, we investigated the expression of PPARϒ (RT-qPCR) in radiation-killed Mtb-stimulated human Mf. The Mtb stimulation of Mf derived from the human line THP1 significantly increased the expression of PPARϒ, while the activation of this receptor by a specific agonist decreased the expression of pro- and anti-inflammatory cytokines (IL-1β and IL-10). As expected, the addition of GC to stimulated cultures reduced IL-1β production, while cortisol treatment together with the PPARϒ agonist lowered the levels of this proinflammatory cytokine in stimulated cultures. The addition of RU486, a glucocorticoid receptor antagonist, only reversed the inhibition produced by the addition of GC. Conclusion The current results provide a stimulating background for further analysis of the interconnection between PPARs and steroid hormones in the context of Mtb infection.